Defining the Caribbean Area and Identity - Tézer, Zita (Acta Hispanica, 2020)
In examining Caribbean identity, it is essential to examine the demarcation of the area, delimit the boundaries, assess how local people have defined or redefined themselves in space and time, and how this is influenced by economics and politics. Obviously the key is the geographic proximity of the Caribbean Sea and its history, which result in many similarities in time, but there is variation, and there are differences. Two significant researchers who investigated the most important common elements like colonization, plantation economy and slavery, Charles Wagley and Sidney Mintz cultural anthropologists, conducted their fieldwork in Brazil, Puerto Rico, Haiti and Jamaica. In defining the “Caribbean” within Plantation America cultural sphere, Charles Wagley took into account the geography, the environment, linguistics, the modes of production, the local histories. Both anthropologists made sociocultural, ethnographic and demographic analyses, comparing the colonial structures in the plantations to delimit the culturally identical area, which, however, today is not followed by geopolitical boundaries, nor is the locals’ perceptions of their own interpretation about the Caribbean area.